(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
On the occasion of the 20th Anniversary of the Convention against Transnational Organized Crime, the section “History and Memory” proposes the second conferences held in Mexico City in 1990 by Giovanni Falcone to members of the United States. In his discourses, Falcone addresses the issues of the Mafia as a global phenomenon and international cooperation, deepening the character of Italian criminal organizations and the main illicit trafficking.